Dead serious : wild hope amid the sixth extinction - Knapp, Eli J. (Torrey House Press, 2021)
"Through personal stories of mishap and adventure, historical vignettes, and scenic detours, professor Eli J. Knapp dissects eighteen critical forces that lie behind the earth's sixth extinction. Drawing from experiences across the globe, Knapp peeks into odd and overlooked corners of natural history, showing how ocean-going tortoises and ghost deer can both instruct and inspire. Full of humor, hope, and self-effacing scientific savvy, Knapp's exploration of our home planet provides welcome respite in a deadly serious subject."--